An analysis of post-vocalic /s-ʃ/ neutralization in Augsburg German: evidence for a gradient sound change - Bukmaier, Véronique; Harrington, Jonathan; Kleber, Felicitas (Frontiers in Psychology, 2014)
The study is concerned with a sound change in progress by which a post-vocalic, pre-consonantal /s-ʃ/ contrast in the standard variety of German (SG) in words such as west/wäscht (/vɛst/~/vɛʃt/, west/washes) is influencing the Augsburg German (AG) variety in which they have been hitherto neutralized as /veʃt/. Two of the main issues to be considered are whether the change is necessarily categorical; and the extent to which the change affects both speech production and perception equally. For the production experiment, younger and older AG and SG speakers merged syllables of hypothetical town names to create a blend at the potential neutralization site. These results showed a trend for a progressively greater /s-ʃ/ differentiation in the order older AG, younger AG, and SG speakers. For the perception experiment, forced-choice responses were obtained from the same subjects who had participated in the production experiment to a 16-step /s-ʃ/ continuum that was embedded into two contexts: /mIst-mIʃt/ in which /s-ʃ/ are neutralized in AG and /və'mIsə/-/və'mIʃə/ in which they are not. The results from both experiments are indicative of a sound change in progress such that the neutralization is being undone under the influence of SG, but in such a way that there is a gradual shift between categories. The closer approximation of the groups on perception suggests that the sound change may be more advanced on this modality than in production. Overall, the findings are consistent with the idea that phonological contrasts are experience-based, i.e., a continuous function of the extent to which a subject is exposed to, and makes use of, the distinction and are thus compatible with exemplar models of speech.